Advances in the Rapid Diagnostic of Viral Respiratory Tract Infections - Gradisteanu Pircalabioru, Gratiela; Iliescu, Florina Silvia; Mihaescu, Grigore; Cucu, Alina Irina; Ionescu, Octavian Narcis; Popescu, Melania; Simion, Monica; Burlibasa, Liliana; Tica, Mihaela; Chifiriuc, Mariana Carmen; Iliescu, Ciprian (Frontiers in Cellular and Infection Microbiology, 2022)
Viral infections are a significant public health problem, primarily due to their high transmission rate, various pathological manifestations, ranging from mild to severe symptoms and subclinical onset. Laboratory diagnostic tests for infectious diseases, with a short enough turnaround time, are promising tools to improve patient care, antiviral therapeutic decisions, and infection prevention. Numerous microbiological molecular and serological diagnostic testing devices have been developed and authorised as benchtop systems, and only a few as rapid miniaturised, fully automated, portable digital platforms. Their successful implementation in virology relies on their performance and impact on patient management. This review describes the current progress and perspectives in developing micro- and nanotechnology-based solutions for rapidly detecting human viral respiratory infectious diseases. It provides a nonexhaustive overview of currently commercially available and under-study diagnostic testing methods and discusses the sampling and viral genetic trends as preanalytical components influencing the results. We describe the clinical performance of tests, focusing on alternatives such as microfluidics-, biosensors-, Internet-of-Things (IoT)-based devices for rapid and accurate viral loads and immunological responses detection. The conclusions highlight the potential impact of the newly developed devices on laboratory diagnostic and clinical outcomes.